Trends of digital transformation of construction organization processes in the conditions of critical influences - Dubinin , D. (Ways to Improve Construction Efficiency, 2022)
The article analyzes theoretical approaches to the formation of the process of digitalization of the economy and digital transformation of construction, interaction of project participants. It was found that critical influences on construction can be called such influences that completely disrupt the construction process of the object, or affect the size of the construction parameters (terms, labor intensity and cost) in such a way that the further construction process is either significantly complicated or impossible at all. Critical impacts can include any changes in the external and internal environment of the construction project, including floods, natural disasters, etc.The review of literary sources made it possible to highlight the main problems, the solution of which is necessary for the proper theoretical justification of the action of critical influences on the process of construction organization and its digital transformation,Theoretical substantiation of the role of critical influences on the transformation of the construction process made it possible to identify the following consequences of the influence of military actions on the construction industry during the war in Ukraine. Such factors were the change in the company’s supply chains and the lack of many material, technical and human resources in construction, the destruction of the existing information structure that needs to be constantly restored, the direction of investment priorities towards the defense of the country, a decrease in investments in digitalization, a significant migration of the population, the growth of cyber threats, the need for cyber protection system, etc.The identification of critical influences on the process of construction organization and on digital transformation will allow enterprises and organizations of the construction complex, various participants in investment and construction projects not only to classify them according to the degree of influence on a separate enterprise, but also to develop a set of preventive or smoothing measures regarding the functioning of participants in the digital environment of the project.